Afectación de los costos a la rentabilidad de la empresa Bananera Santa María durante el periodo 2019 - Gómez Loor, Orvi Emiliano (2021)
Today companies need to be efficient to make agile decisions andconcrete, in order to survive on competition, and market adversities changing people that the company must convince and attract them to buy their products is for this reason that companies need to manage their costs appropriately, in this way they will be certain of the information and will be able to give a step into the future by setting measurable goals and objectives in the short medium and long in this way, proper cost management allows the company to optimize your winnings. In this case study, the costs incurred in the study will be analysed banana production during the period 2019 in the banana company "Santa María".